Effect of Nitrogen and Water Use on Yield And Storability of Onion (Bangladesh Journal of Agricultural Research, 2023)
A Field experiment was conducted at Regional Spices Research Centre, BARI, Gazipur and Spices Research Sub-Centre, BARI, Lalmonirhat to find out the water and nitrogen use efficiency of onion (Allium cepa L.) as influence by different levels of soil moisture regimes and nitrogen doses during rabi season of 2020-2021. The experiment was designed in Factorial Randomized Complete Block Design having three replications. The treatment composed of three soil moisture regiems (10%, 20% and 30% depletion of soil moisture over field capacity) and three nitrogen doses (150, 100 and 75 kg ha-1). The individual as well as interaction effect of soil moisture and nitrogen levels showed significant effect on yield and yield contributing parameters, storability, nitrogen and water use efficiency except the TSS of onion. The highest bulb yield (21.49 t ha-1 in Gazipur & 22.79 t ha-1 in Lalmonirhat), marketable bulb yield (18.0 t ha-1 in Gazipur & 20.0 t ha-1 in Lalmonirhat), harvest index (598.0% in Gazipur & 607.9% in Lalmonirhat) were recorded when the crop irrigated at 10% depletion of field capacity and plant supplied with 100kg Nha-1. Similarly, the maximum nitrogen use efficiency (54.74% in Gazipur & 61.38% in Lalmonirhat) and the maximum water use efficiency (105.76 kg ha-1 mm-1 in Gazipur & 108.06 kg ha-1 mm-1 in Lalmonirhat) were also observed from the above mentioned treatment combinations. Total PLW was higher (16.3% in Gazipur and 21.1% in Lalmonirhat) with irrigation was given applied at 10% depletion of field capacity and application of 150 kg N ha-1 during 120 days of storage.Bangladesh J. Agril. Res. 47(1): 119-142, March 2022